A new model of implant-related osteomyelitis in the metaphysis of rat tibiae. Issue 1 (December 2016) - Harrasser, Norbert; Gorkotte, Johannes; Obermeier, Andreas; Feihl, Susanne; Straub, Melanie; Slotta-Huspenina, Julia; von Eisenhart-Rothe, Ruediger; Moser, Walter; Gruner, Philipp; de Wild, Michael; Gollwitzer, Hans; Burgkart, Rainer
Abstract Background Animal models serve as an important tool to understand peri-implant infection. Most of the models use high bacterial loads (>104 colony forming units, CFU) to provide high infection rates. Therefore these animals evolve rather similarly, making comparison between groups and statistical analysis possible. On the other hand, to mimic clinical constellation of surgery-related infections the use of low amounts of bacteria would be more advantageous. Methods We developed a metaphyseal rat model of peri-implant bone infection with low amount of bacterial loads (102 and 103  CFU ofStaphylococcus aureus ) and investigated osseointegration of the implants coated with hydroxyapatite (HA) and low-dosed HA-silver (HA-Ag). Non-infected implants served as controls. After 6 weeks rats were sacrificed and implants evaluated for osseointegration and infection. Results Infection of implanted devices was reliably induced, independently whether 102 or 103  CFU ofS. aureus were inoculated and HA or HA-Ag coated implants were used. No systemic infection was present in any of the animals at the time of sacrifice, and no animal developed acute infection requiring premature sacrifice. All CFU counts of the implant and the bone at sacrifice were significantly higher than the inoculated load (p  < .05). All sterilely inserted implants showed excellent osseointegration and no infection. Conclusions Our present study of a rat tibia model reliably induced osteomyelitis in the metaphysis with low-doses of bacteria. The addition of low-dosed Ag to the implant coating was not able to reduce the infection rates. The results demonstrate that it is possible to develop a model of implant-related osteomyelitis in rats with low amounts of bacteria to better mimic clinical constellations. No other promoters of infection besides insertion of the screw implant were used in this model.